Análise do estado nutricional da população idosa da comunidade de Cuiabá (MT) - Rodrigues, Rosilene Andrade Silva (2012)
Introduction: The elderly population has increased worldwide and nutritional status of under-or overfeeding negatively impact the health and burden the public health system. Objective: To evaluate the nutritional status to describe and compare the sociodemographic profile, to estimate the prevalence of undernourished, normal weight, overweight and obesity by the Mini Nutritional Assessment (MNA) and body mass index (BMI), and establish five new reference values for circumferences of the calf, arm and abdomen in the elderly population to predict nutritional status. Methods: A crosssectional study with 513 elderly were interviews of evaluated 391 subjects with complete data, age ≥ 65 to 93 years, representative of the urban population of CuiabáMT. We measured body weight in kilograms and height in meters, using a digital platform scale (G-Tech ®, capacity 180 kg, automatic, accurate to 0.1 kg) and height measured by tape measure rigid (Starrett ®). Circumferences were measured with a flexible tape, inextensible, accuracy of 0.1 cm, with the subject standing in the right hemibody for the relaxed arm circumference (CB), the abdomen (CA), calf (CP) in centimeters (cm). We calculated the BMI for the elderly (kg/m2 ) and mini nutritional assessment (MNA,> 17 "malnourished" above and up to 23.5 "risk of malnutrition" and other scores up to 30 "well nourished". We used analysis of sample distribution by the Shapiro Wilk, calculated the relative and absolute frequencies, with Spearman's test for multiple comparisons and the Kruskal Wallis test of significance p ≤ 0.05. Results: The median age observed in the elderly population was 71 years and 64% women and 36% men. The correlation of age with: CB (r =- 0.180, p<0.001), CP (r =- 0.202; p<0.001). It was observed throughout the sample average of 27 ± 5 in BMI calculation adapted for seniors, 15% classified as malnourished, undernourished risk of 13%, 24% normal weight, overweight and obesity has reached 33% of this population 16% . Correlations of BMI with: CB (r = 0.798, p<0.001), CA (r = 0.823, p<0.001). Obtained at MNA in the whole sample the average score of 25 ± 3, which classified 14% of elderly "malnourished" 12% "risk of malnutrition" and 74% as "well nourished" by both genders. Other correlations: CB and CA (r=0.798, p<0.001) CB and CP (r=0.648, p <0.001), CP and CA (r=0.496, p<0.001), CP and BMI (r=0.605, p<0.001). Classification by eutrophic calf circumferences of 33 cm, 29 cm arm, and abdomen in 95 cm in both sexes to predict the nutritional status of elderly. Conclusion: It is concluded that most elderly patients evaluated had inadequate nutritional status, overweight or underweight, suggesting the importance of evaluating this condition for the prevention and treatment of comorbidities and maintenance of physical independence. However, there was a higher prevalence of overweight than the deficit, overeating may present greater risk of malnutrition in this population. In this sense, the anthropometric measures were better able to stratify the nutritional status of the MNA. Still, the proposed simple measurements of arm circumference, calf and abdomen, with the aim of assessing the nutritional status, seem to have been adequate for this purpose. We intend in future studies associate blood biochemical markers to confirm this reasoning. This information may contribute to the planning of public health policies.